2020
DOI: 10.1111/inm.12805
|View full text |Cite
|
Sign up to set email alerts
|

Peer support worker training: Results of the evaluation of the Experienced Involvement training programme in Switzerland and Germany

Abstract: The ‘Experienced Involvement’ (EX‐IN) training programme prepares and certifies individuals who have experienced mental health problems to work as peer support workers and to support others challenged by similar conditions. We aimed to assess the impact of the EX‐IN training on hope, self‐efficacy, introspection, stigma resistance, personal recovery, health‐related quality of life and employment in participants. Data was collected using standardized assessment instruments before the training started (t1) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Of the seven papers that addressed employment outcomes, six indicated an increase in employment rates (in any capacity) related to the mental health system at both follow-up (Franke et al, 2010;Gammonley & Luken, 2001;Hegedüs et al, 2016) and post-training periods; Hegedüs et al, 2021;Rapp et al, 2008;Wolf, 2014). One found that more completers were employed in a related field or in accredited settings compared to non-completers (Horwitz et al, 2020).…”
Section: Post-training Employmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the seven papers that addressed employment outcomes, six indicated an increase in employment rates (in any capacity) related to the mental health system at both follow-up (Franke et al, 2010;Gammonley & Luken, 2001;Hegedüs et al, 2016) and post-training periods; Hegedüs et al, 2021;Rapp et al, 2008;Wolf, 2014). One found that more completers were employed in a related field or in accredited settings compared to non-completers (Horwitz et al, 2020).…”
Section: Post-training Employmentmentioning
confidence: 99%
“…Eight studies reported improved perception of self (e.g., self-esteem and confidence; Blixen et al, 2015;Gerry et al, 2011;King et al, 2009;Meehan et al, 2002;Simpson et al, 2014;Wolf, 2014), self-efficacy (Hegedüs et al, 2021), and improved self-image (Weeks et al, 2006). Six studies reported short to long-term improvements in healthrelated measures (i.e., improved psychosocial wellbeing and quality of life) following training (Atif et al, 2019;Gammonley & Luken, 2001;Gerry et al, 2011;Joo et al, 2018;Stockmann et al, 2019;Weeks et al, 2006).…”
Section: Personal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Peers are typically recruited from within the client pool of a service and are usually given some basic training for the role of offering support to other individuals, to aid their journey to recovery or treatment completion (Mowbray 1998, Hegedus et al 2020. This support could take the form of helping people attend their appointments, take their medication or change their lifestyle to optimise their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This support could take the form of helping people attend their appointments, take their medication or change their lifestyle to optimise their recovery. The flexibility of peer work can present an opportunity to re-enter the labour market for a group that can struggle with the responsibility of fixed employment (Kennedy et al 2019, Hegedus et al 2020, Miler et al 2020. However this volunteer role is characterised by instability and insecurity (Greer et al 2020, Otte et al 2020.…”
Section: Introductionmentioning
confidence: 99%